The Gastronomic Tourism present in the Bioceanic Route in Mato Grosso do Sul - Arguelho, Joelma Fernandes (2023)
The subject of this article is the possibility of exploring and discovering the potential of the gastronomy in the state of Mato Grosso do Sul, more specifically in the municipalities that make up the Bioceanic Route, aiming to highlight the importance and attractions of gastronomic tourism. Additionally, the intention is to promote the Bioceanic Route as a tourist destination for gastronomy enthusiasts, highlighting the unique foods and gastronomic experiences that can be found along the journey. The analytical trajectory of this work was based on bibliographic review and analysis of documented data from public institutions, with the intention of obtaining updated information and knowledge on the subject. The results obtained indicate that, up to the present moment, there are no financial investments or discussions about the implementation of a gastronomic route along the Bioceanic Route. The route lacks fueling stations, which, once established, tend to offer fast food and ready-made meals for truck drivers who transit through the region, considered a logistics hub. However, one initiative does not invalidate the other, as while it is necessary to provide quick and affordable food to meet the dietary needs of those who transit for work, there is also another audience that will enjoy the route for leisure travel. Therefore, the creation of a gastronomic circuit, which includes restaurants, cafes, local producers, food fairs, and other establishments, offering an authentic experience of the regional cuisine, brings numerous benefits for local development. In summary, the creation of a gastronomic route can be a promising opportunity for sustainable local development, valuing regional cuisine, stimulating tourism, and strengthening the economy. This project requires planning, community involvement, and strategic partnerships to achieve success.